Philippians - Johnson, Dennis E. (Dennis Edward) (Phillipsburg, New Jersey : P & R Publishing, 2013)
"The truth revealed behind the phrase 'for me to live is Christ' transforms our responses to present imperfections and future hope. Johnson's commentary-grounded in pastoral application-is ideal for sermon preparation and devotional reading"--Publisher description.
Captivated by Christ Jesus (Philippians 1:1-2) -- He Finishes What He Starts (Philippians 1:3-8) -- A Pastor's Passionate Prayer (Philippians 1:9-11) -- Prison is Great--Wish You Were Here! (Philippians 1:12-18a) -- A Tough Choice, but One Supreme Goal (Philippians 1:18b-26) -- Solidarity in Suffering (Philippians 1:27-30) -- Hearts Turned Inside Out (Philippians 2:1-4) -- The King Who Stooped to Conquer (Philippians 2:5-8) -- The Son Exalted for the Father's Glory (Philippians 2:9-11) -- Bright Stars in a Dark Sky (Philippians 2:12-18) -- Living Replicas of the Servant of the Lord (Philippians 2:19-30) -- Trading My Rags for His Robe (Philippians 3:1-11) -- The Restless Race of Those Who Rest in Grace (Philippians 3:12-16) -- A Tale of Two Citizenships (Philippians 3:17-21) -- Stand Together (Philippians 4:1-3) -- Antidotes to Anxiety (Philippians 4:4-9) -- Cracking the Contentment Code (Philippians 4:10-13) -- The Puzzling Partnership of Getting by Giving (Philippians 4:14-23).
Includes bibliographical references (page 317) and indexes.
Keywords: Bible. -- Commentaries